Kesadahan Air Sumur Warga Desa Ligarmukti Kabupaten Bogor - Angki Purwanti; Tri Pasetyorini (CV. CENDIKIA JENIUS INDONESIA, 2024)
Ligarmukti is a village in Bogor Regency which is crossed by limestone hills. The source of water consumed by village residents comes from dug wells which characterize hard water. The aim of the research was to determine the total hardness level of the well water of residents of Ligarmukti village RT/RW 12/06 Bogor Regency which is used for drinking and cooking purposes. The research design was descriptive observational with laboratory examination. As a sample, 29 well water was used taken from 29 wells dug by residents of RT/RW 12/06 Ligarmukti village, Bogor Regency, with a population of 35 wells. Determination of total hardness is carried out using complexometric titration. Water hardness is categorized based on the International of Drinking Water from WHO (2017) into